La identidad docente de profesores de posgrados médicos y quirúrgicos en un hospital universitario: una mirada desde las historias de vida. - Salcedo Monsalve, Alejandra (Revista Ciencias de la Salud, 2016)
This article shows the results of a research in which I decided to analyze the narratives of professors of medical and surgical specialties in a university hospital in the city of Bogota, and interpret their teaching experiences, to learn some elements of their identity and the pedagogical knowledge they have built. A qualitative study was conducted from the hermeneutical historical approach, using life stories. Five teachers participated voluntarily. An analysis of the narratives focused on the meaning and the interpretation of the findings in the light of pedagogical theory was performed. In relation to teacher identity, the specialists became teachers unintentionally as a response to own labor requirements of the job at the university hospital. The construction process of the teachers started from their years of schooling, and pedagogical practice has a strong influence on what they learned from their own teachers. The academic activity is being undertaken by the major motivation vocation, expressions of thanks of their students and satisfaction for achieving the proposed learning objectives. The lack of teacher training creates tension and concern among teachers, which could be prevented with teacher education programs.